Urgent resection of a giant left atrial appendage aneurysm and mitral valve replacement in a complex case of Hurler-Scheie syndrome. (5th November 2015) - Brazier, Andrew; Hasan, Ragheb; Jenkins, Petra; Hoschtitzky, Andreas
Abstract : Hurler-Scheie syndrome is a rare lysosomal storage disease affecting the cardiovascular system. Besides the cardiac manifestations, it presents with complications from abnormal proteoglycan deposition in soft tissues in many locations, resulting in joint contractures, paraplegia, impaired vision, airway narrowing and restrictive lung function, to name a few. There are very few reports of surgical management of valvular heart disease due to mucopolysaccharidosis (MPS). We describe the successful management of a patient with an extremely challenging case of mitral valve stenosis and a giant left atrial appendage aneurysm due to MPS type 1 (Hurler-Scheie syndrome). The patient underwent mitral valve replacement and excision of the giant left atrial appendage aneurysm; a similar case has not been previously reported.